Streamlined boiling lysis DNA extraction for Gram-positive aquaculture pathogen Streptococcus agalactiae - Habib, Syahir; Azmai, Mohammad Noor Amal; Md Yasin, Ina-Salwany; Masdor, Noor Azlina (Springer Science and Business Media Deutschland GmbH, 2024)
Accurate genetic analysis is essential for the detection of pathogens as it necessitates suitable DNA extraction methods tailored to specific microorganisms such as Gram-positive bacteria. This study examined several commercial and simplified DNA extraction methods for their suitability in isothermal downstream applications. Extracted DNA was assessed using spectrophotometry, electrophoresis, polymerase chain reaction (PCR) and loop-mediated isothermal amplification (LAMP) while its stability was inspected after five months of storage. The findings revealed variations in DNA yield, purity and integrity among the extraction methods. While extraction kits demonstrated high yield and purity, the in-house extraction techniques showed incoherent correlation between yield and purity, yet showed promise for a streamlined extraction process. The DNA acquired from all methods yielded positive amplification in PCR and LAMP. DNA extracted by kits exhibits prolonged stability than those obtained via boiling lysis. Both methods offer distinct advantages, with commercial kits providing longer stability and high-quality DNA while boiling lysis stands out for its simplicity, with shorter handling and processing periods. This study emphasizes selecting ideal extraction methods for Streptococcus agalactiae, in the prospect of aquaculture settings. In particular, successful LAMP reaction suggests that boiled extracts are feasible enough for detection, and suited for point-of-care (POC) testing where prompt detection of aquatic pathogens is often critical. Ultimately, the choice of method should be contemplated on a case-by-case basis such as the study goals, intended settings, and type of samples. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.